Adoption of cage farming has enhanced livelihood security of the reservoir fishers: Evidence from Jharkhand state of India - Pandit, Arun; Debroy, Piyashi; Chandra, Ganesh; Roy, Aparna; Chakraborty, L; Das, B K; Biswas, D K (Journal of the Inland Fisheries Society of India, 2021)
t The reservoirs of India, due to high biogenic production potential, form a very important fishery resource. In addition to contributing to fish production, they also play a significant role in livelihood and nutritional security to a large section of an economically underprivileged population in India. Livelihood security implies the sustainable assurance of the means of livelihood for the people. Development of livelihood security index could be one of the most important social indicators for assessing the quality of life, coupled with meeting the basic needs of human beings. The present study was conducted in the state of Jharkhand which is one of the early adopters of cage culture in India. Primary data were collected through personally interviewing 100 fishermen families in 2018. Data were collected on the different livelihood capitals viz., natural, physical, financial, human, and social capital. The study found that overall, the livelihood security of the fishers was low to moderate. The Livelihood Security Index is better in the case of cage fishers. Cage farming has contributed to both social capital formation and financial empowerment. They have also accumulated some durable assets due to improvements in household income. These findings show the importance of cage culture in enhancing the livelihood of the fishers. However, the study found much scope for further improvement of the indices. The fishers should be motivated to rear animals to supplement their income to enhance natural capital. Support needs to be provided for the purchase of farm poultry birds, small ruminants, etc. To enhance the social capital, there is a need to provide proper counseling for fishers for the formation of SHGs, youth clubs, and Farmer's Interest Groups. The co-operatives of the fishers should also be active and dynamic.